PENDIDIKAN ANTI KORUPSI SEBAGAI STRATEGI DALAM PENGEMBANGAN BUDAYA ANTI KORUPSI PADA GENERASI MUDA DI INDONESIA - I Komang Sri Cahyadi (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
Prevention of corruption crimes by using educational facilities based on anti-corruption is a form of effort to prevent corrupt behavior with anti-corruption values contain ed in anti-corruption education. The problem, regarding corruption which has become a habit in the bureaucracy in Indonesia, is a challenge in itself in eradicating it. Anti-corruption education in developing an anti-corruption culture with anti-corruptive values ​​can be a strategy towards an Indonesia that rises from the level of corruption that has plagued Indonesia for a long time. This study uses a research method based on normative legal research by taking a literature approach in the form of legislation as well as related legal literature. From this research that development of culture based on anti-corruption in younger generation in an effort to fight against corruption as an old disease of Indonesian Nation.